(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2023)
Several conventional and unconventional digitization tools have been used to improve viewing and acquisition of information in the field of sedimentology and sedimentary petrology, in geology and in science and technology in general. Slide scan images of sedimentary rock thin- sections provide inexpensive, very good, whole thin-section views at magnifications similar to those of the conventional microscope. This paper demonstrates how slide scan images can be obtained and how they can quickly be used to gather detailed textural, structural and compositional information of sandstones at microscopic scale. The method has been used in studying features such as grain size, grain shape, fabric, contact between grains, graded bedding, cross lamination and porosity without the need for polarizing microscope and photomicrograph. This unpopular, unconventional method is not known by most researchers even though it can provide alternative means of obtaining vital geological information relevant to both the academia and the industry. This method is also recommended to teachers in low- equipment universities and research centers where research petrological microscopes are either absent or inadequate or during periods of lock-down.